PTU-173 Long Term Follow Up After Successful Radiofrequency Ablation For Barrett's Related Neoplasia Is Essential To Diagnose Recurrent Disease: Data From The United Kingdom Patient Registry. (9th June 2014) - Haidry, RJ; Banks, M; Gupta, A; Butt, M; Fullarton, G; Smart, H; Morris, J; Willert, R; Narayanasamy, R; Rodriguez-Justo, M; Novelli, M; Lovat, L
Abstract : Introduction: Radiofrequency ablation (RFA) for patients with Barrett's oesphagus (BE) related mucosal neoplasia has been shown to be safe and effective. Endoscopic mucosal resection (EMR) for visible lesions followed by RFA is now recommended practice for these patients. Although success rates are high for disease reversal at 12 months it is appreciated that recurrence after eradication of dysplasia and intestinal metaplasia (IM) can occur in up to 25% of patients. There is still debate as to what are the optimum endoscopic follow up intervals after successful treatment. Methods: We examine prospective data from United Kingdom (UK) registry of patients undergoing RFA/EMR for BE related neoplasia over the past 5 years. We aim to establish the frequency and time of recurrences after successful treatment. Before RFA, visible lesions were removed by EMR. Thereafter patients underwent RFA every 3 months. Biopsies were taken at 12 months for clearance of dysplasia (CR-D) and BE (CR-IM). Durability and recurrence for those with successful eradication was analysed. After successful treatment patients were followed up at 3 monthly for the first year, 6 month intervals for second year and annually thereafter. Biopsies were taken from 1cm below the neo z-line and from the previously treated BE segment. Results: A total 508 patients have been treated. At 12 months CR-D was 85% (428/508) and CR-IM 70% (354/508). For those with successful outcomes at 12 months who remain in follow up, median time to their most recent biopsy is 20 months from start of treatment (range 2–72). Kaplan Meier survival statistics predict that at 5 years 75% of patients are likely to be free of dysplasia and 74% free of IM. Median time to recurrence for dysplasia is 380 days (IQR 177–619), and IM 573 days (IQR 237–816). There were 21 patients with recurrent dysplasia, 48% occurred within the first year after successful treatment, 29% in the second year, 14% in the third year and only 9% after 4 years. Conclusion: The majority of recurrences after successful RFA occur within the first 2 years (16/21–76%). These date support the practice of vigilant long term follow of patients who are fit for endoscopy after treatment with RFA. More intensive and frequent follow up should take place in the first 2 years when the majority of recurrences occur. Thereafter annual follow up appears adequate. All collaborators of the UK RFA registry are acknowledged for their contributions to this work. Disclosure of Interest: None Declared.